Parametric Studies Into Creep and Shrinkage Characteristics in Railway Prestressed Concrete Sleepers - Li, Dan; Kaewunruen, Sakdirat; Robery, Peter; Remennikov, Alex M. (Frontiers in Built Environment, 2020)
It is well known that prestressed concrete is highly suitable for railway sleepers because of its many advantages in performance, maintenance, sustainability, and construction. Prestressed concrete design can improve structural performance since the prestress enables fully compressed cross sections. Higher tensile resistance of prestressed concrete can then take place. However, longer-term performance and durability of concrete sleepers largely depends on creep and shrinkage behaviors. On this ground, the effects of time-dependent phenomena on prestressed concrete sleeper are investigated in this study. In the past decades, a number of material models have been established to estimate creep and shrinkage behavior, but those were mostly based on a generic reinforced concrete design concept. The common uses of prestressed concrete have led to practical concerns by practitioners whether those existing predictive models could be realistically applied to prestressed concrete applications. Due to a relatively higher initial elastic shortening in prestressed concrete, the creep and shrinkage effects should be critically reevaluated among flexural members. This study embarks on comparative studies into the effects of creep and shrinkage on prestressed concrete railway sleepers. A thorough comparison between prediction models underpinned by European Standard Eurocode 2, American Standard ACI, and Australian Standard AS3600-2009 enables new insights into the time-dependent performance of railway concrete sleepers installed in various locations or in different continents. This implies that the durability of railway concrete sleepers can be undermined differently when exposed to different conditions even in the same rail network. The insights stemmed from this study will help track engineers to better design and maintain railway infrastructure, improving asset management efficacy.